Inhibitory effects of Spirulina in zymosan-induced arthritis in mice - Diadelis Remirez; Ricardo González; Nelson Merino; Sandra Rodriguez; Odelsa Ancheta (Hindawi Limited, 2002)
The anti-inflammatory effect of microalgae Spirulina was studied in zymosan-induced arthritis in mice. Four days after the intra-articular injection of zymosan (15 mg/ml), Spirulina (100 and 400 mg/kg per-orally) was administered to animals for 8 days. The mice were than killed and β-glucuronidase was measured in the synovial fluid. Each knee joint was totally removed for histopathological studies. Spirulina significantly reduced the levels of β-glucuronidase that had been increased by zymosan. Histopathological and ultrastructural studies showed inhibition of the inflammatory reaction, whereas no destruction of cartilage, well-preserved chondrocytes, and normal rough endoplasmic reticulum and mitochondria were seen. The anti-arthritic effect exerted by Spirulina as shown in this model may be at least partly due to the previously reported anti-inflammatory and antioxidative properties of its constituent, phycocyanin. To our knowledge, this is the first report on the anti-inflammatory effect of Spirulina in an experimental model of arthritis.